Using Podcasts to Enhance Students’ Public Speaking Skills: English - Putri Kinasih; Sandrina Ariyani Widjaja (JOEY: Journal of English Ibrahimy, 2025)
Developing one's public speaking skills was  necessary. And, podcasts can be used as a medium for practicing public speaking. In particular, podcasts were a popular form of media among Indonesians. This study adopted the mixed-method approach. The participants of this study were the students from the English for Public Speaking class (BIC06), a combined class from three majors, which were  Psychology, System Information, and English studies at UBM. There were 34 participants, consisting of 15 females and 19 males. The research was started by conducting a pretest. Then, the researchers gave treatment related to podcast production and supporting ideas. Afterward, the participants produced podcasts as their post-tests. The participants' pre-test and post-test were analyzed based on a scoring rubric by a rater. Finally, the writers conducted a semi-structured interview. The results showed that the student's public speaking abilities are progressing from Average to good to Good to excellent. Also, this study supports the idea that students' confidence, fluency, and pronunciation improved when they produced podcasts as part of their public speaking exercises. In terms of accuracy, the complete data set helped them to have a flowing conversation, which resulted in fluency. The conversational podcast format is credited with the increase in score. Last, despite providing a safe space, podcast projects also resulted in giving the students a too comfortable environment as they presented ideas among friends.